An Alignment Medium for Measuring Residual Dipolar Couplings in Pure DMSO: Liquid Crystals from Graphene Oxide Grafted with Polymer Brushes. (17th February 2016) - Zong, Wen; Li, Gao‐Wei; Cao, Jiang‐Ming; Lei, Xinxiang; Hu, Mao‐Lin; Sun, Han; Griesinger, Christian; Tan, Ren Xiang
Abstract: Residual dipolar couplings (RDCs) have attracted attention in light of their great impact on the structural elucidation of organic molecules. However, the effectiveness of RDC measurements is limited by the shortage of alignment media compatible with widely used organic solvents, such as DMSO. Herein, we present the first liquid crystal (LC) based alignment medium that is compatible with pure DMSO, thus enabling RDC measurements of polar and intermediate polarity molecules. The liquid crystals were obtained by grafting polymer brushes onto graphene oxide (GO) using free radical polymerization. The resulting new medium offers several advantages, such as absence of background signals, narrow line shapes, and tunable alignment. Importantly, this medium is compatible with π‐conjugated molecules. Moreover, sonication‐induced fragmentation can reduce the size of GO sheets. The resulting anisotropic medium has moderate alignment strength, which is a prerequisite for an accurate RDC measurement.